Coverage Range and Cost Comparison of Remote Antenna Unit Designs for Inbuilding Radio over Fiber Technology - Razali Ngah; Teguh Prakoso; Tharek Abdul Rahman (Journal of ICT Research and Applications, 2008)
Future communication needs to be ubiquitous, broadband, convergent, and seamless. Radio over fiber (RoF) technology is one of the most important enabler in access network for the technologies. Adoption of RoF faces bottleneck in optoelectronics, that they are still expensive, high power consumption, and limited in bandwidth. To solve the problem, transceiver in remote antenna unit (RAU) is developed, i.e. electroabsorption transceiver (EAT) and asymmetric FabryPerot modulator (AFPM). This paper compares their coverage range and cost in providing WCDMA and WLAN services. Needed gain of RF amplifier for supporting picocell is also discussed.